2022
DOI: 10.3233/shti220346
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Fatigue-Management in People with Post-Acute COVID-19 Syndrome – Experiences with the “Untire” App

Abstract: Background: Many patients suffering from post-acute COVID-19 syndrome must deal with fatigue. They need physical and psychological support, strengthening, and adaption of their individual lifestyle. The use of apps can foster fatigue management. Objectives: The aim of this study was to analyse experiences of patients with fatigue caused by post-acute COVID-19 syndrome after using Untire for more than two weeks. Methods: A qualitative research design was chosen to identify user-experience after using the app. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 0 publications
0
13
0
3
Order By: Relevance
“…Fatigue not caused by an effort and persisting after rest, non‐restorative sleep, and sore throat are observed more frequently in women compared to men. Besides some studies have shown the usefulness of mobile applications designed for cancer patients in treating fatigue due to COVID‐19 (Ruckser‐Scherb et al., 2022 ), future research is needed in order to better assess the course of post‐COVID fatigue and find appropriate treatment strategies (Manu, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue not caused by an effort and persisting after rest, non‐restorative sleep, and sore throat are observed more frequently in women compared to men. Besides some studies have shown the usefulness of mobile applications designed for cancer patients in treating fatigue due to COVID‐19 (Ruckser‐Scherb et al., 2022 ), future research is needed in order to better assess the course of post‐COVID fatigue and find appropriate treatment strategies (Manu, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in the 3 pretest studies, 27 (adults from Ireland) [ 20 ], 10 (adults living in underserved communities in the United Kingdom) [ 24 ], and 7 (adults in Austria) [ 4 ] participants took part, and from pre- to postintervention, 5 [ 20 ], 2 [ 24 ], and 0 [ 4 ] participants dropped out. Thus, the dropout rates were 0%-20%.…”
Section: Resultsmentioning
confidence: 99%
“…In the 3 pretest studies, post-COVID/long-COVID symptoms were defined as persisting respiratory symptoms after a COVID-19 infection (>28 days) [ 20 ], as persisting symptoms that resulted from a COVID-19 infection [ 24 ], and as fatigue symptoms after a COVID-19 infection [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations